Students’ Participation In English Class Based On Deep Learning Approach - Anjelia, Devi; Susanti, Elis (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
Student participation is an important factor in the success of English learning, particularly in developing speaking skills in EFL classrooms. However, many students still show low participation during classroom activities. This study aims to describe students’ participation during the implementation of the Deep Learning approach in learning the topic “Nice to Meet You” for seventh-grade students at SMPN 1 Kotabumi. This research employed a qualitative descriptive design involving 35 students selected through purposive sampling. Data were collected through classroom observation, questionnaires, and documentation and analyzed using qualitative analysis consisting of data reduction, data display, and conclusion drawing. The findings revealed that the Deep Learning approach encouraged students’ participation through behavioral, cognitive, and emotional engagement. Students actively participated in speaking practices, showed attention and understanding of the learning material, and demonstrated positive attitudes toward the learning activities. These findings indicate that the Deep Learning approach can create a meaningful and interactive learning environment that supports students’ participation in EFL classrooms